Comparison between rectal and infrared skin temperature in the newborn. Issue 1 (21st December 2007) - De Curtis, Mario; Calzolari, Flaminia; Marciano, Alessandra; Cardilli, Viviana; Barba, Gianvincenzo
Abstract : The reliability of measurement of body temperature using a new infrared skin thermometer was evaluated in 107 newborns. The use of the device was associated with low operator-related variability and acceptable limits of agreement with the temperature measured with a rectal mercury thermometer. Use of the infrared skin thermometer is a comfortable and reliable way of measurement of body temperature in newborns.